Wireless network Risk Assessment Model and Application - JianGang Tang (Institute of Advanced Engineering and Science, 2014)
Wireless network makes up the wired network shortcomings. With the popularity of the WiFi terminal, the security threats are constantly upgrading, and the security issues have been plaguing the legitimate user. In this paper we had analyzed the risks mechanism of WLAN for network resources, and designed an assessment model of security risk. When the incidents of network security which caused for vulnerability factors had been occurred, the model can be used to assess the consequences and impact on WLAN. The model achieves the network security early warning and control by scientific measurement and evaluation of the WLAN security risks. Wireless network security is not only with authentication, encryption, integrity testing and other technology-related, but also need intrusion detection systems, firewalls and other technology cooperation, so it’s a multi-layered problem. DOI: http://dx.doi.org/10.11591/telkomnika.v12i6.5446